Does austerity pay off? - Benjamin Born; Gernot J. Müller; Johannes Pfeifer (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2015)
We ask whether cuts of government consumption lower or raise the sovereign default premium. To address this question, we set up a new data set for 38 emerging and advanced economies which contains quarterly time-series observations for sovereign default premia, government consumption, and output. We find that whether austerity pays off depends on a) initial conditions and b) the time-horizon under consideration. Spending cuts in times of fiscal stress raise default premia, but lower premia in benign times. These findings pertain to the short run. Austerity always pays off in the long run, but particularly so if initial conditions are bad.
Keywords: E62; E43; C32; 330; Fiscal policy; austerity; sovereign risk; default premium; local projections; panel VAR; fiscal stress